Macro and Trace Elements in Hemp (Cannabis sativa L.) Cultivated in Greece: Risk Assessment of Toxic Elements - Zafeiraki, Effrosyni; Kasiotis, Konstantinos M.; Nisianakis, Paul; Machera, Kyriaki (Frontiers in Chemistry, 2021)
The accumulation of hazardous contaminants in Cannabis sativa L. raises warning signs regarding possible adverse effects on human health due to the consumption of herbal medicines and/or other herbal edible products made from cannabis. Thus, there is an urge to investigate the levels of hazardous contaminants, such as heavy metals in cannabis plant. In the present study, 29 macro and trace elements, including both beneficial and toxic elements (heavy metals and metalloids) were investigated in 90 samples of cannabis sativa L. collected from Greece. According to the results, the detected concentrations of macro elements in the leaves/flowers of cannabis ranged between 28 and 138378 ppm, and of trace elements between 0.002 and 1352.904 ppm. Although the concentrations of elements varied among the samples, their accumulation pattern was found to be similar, with the contribution of toxic elements to the total concentration of trace elements being below 1%. The detected levels of the most toxic elements were below the prescribed limits established by WHO, while the calculated THQ and CR values, showed no risk (non-carcinogenic and carcinogenic) for the population exposed to the current cannabis samples. Positive correlation between the concentration of elements and cannabis geographical origin and variety was observed. Cannabis leaves/flowers were more contaminated with trace and macro elements compared to seeds.